UVA-induced cyclobutane pyrimidine dimers form predominantly at thymine–thymine dipyrimidines and correlate with the mutation spectrum in rodent cells - Rochette, Patrick J. (Oxford University Press, 2003)
Ligation-mediated PCR was employed to quantify cyclobutane pyrimidine dimer (CPD) formation at nucleotide resolution along exon 2 of the adenine phosphoribosyltransferase (aprt) locus in Chinese hamster ovary (CHO) cells following irradiation with either UVA (340–400 nm), UVB (295–320 nm), UVC (254 nm) or simulated sunlight (SSL; λ > 295 nm). The resulting DNA damage spectrum for each wavelength region was then aligned with the corresponding mutational spectrum generated previously in the same genetic target. The DNA sequence specificities of CPD formation induced by UVC, UVB or SSL were very similar, i.e., in each case the overall relative proportion of this photoproduct forming at TT, TC, CT and CC sites was ∼28, ∼26, ∼16 and ∼30%, respectively. Furthermore, a clear correspondence was noted between the precise locations of CPD damage hotspots, and of ‘UV signature’ mutational hotspots consisting primarily of C→T and CC→TT transitions within pyrimidine runs. However, following UVA exposure, in strong contrast to the above situation for UVC, UVB or SSL, CPDs were generated much more frequently at TT sites than at TC, CT or CC sites (57% versus 18, 11 and 14%, respectively). This CPD deposition pattern correlates well with the strikingly high proportion of mutations recovered opposite TT dipyrimidines in UVA- irradiated CHO cells. Our results directly implicate the CPD as a major promutagenic DNA photoproduct induced specifically by UVA in rodent cells.